An Enhanced LVRT Scheme for DFIG-based WECSs under Both Balanced and Unbalanced Grid Voltage Sags. Issue 11 (3rd July 2017) - Mohammadi, Jafar; Afsharnia, Saeed; Ebrahimzadeh, Esmaeil; Blaabjerg, Frede
Abstract: Due to the latest grid codes, wind energy conversion systems (WECSs) are required to remain connected to grid under grid voltage sags and supply reactive power into the grid. So, this paper proposes an enhanced scheme to improve low-voltage ride through (LVRT) capability of doubly fed induction generator (DFIG)-based WECSs under both balanced and unbalanced grid voltage sags. The proposed scheme is composed of active and passive LVRT compensators. The active compensator is performed by controlling the rotor- and grid-side converters of the DFIG to decrease the stator flux oscillations and inject reactive power into the grid. The passive compensator is based on a three-phase stator damping resistor (SDR) located in series with the stator windings. The proposed scheme decreases the negative effects of grid voltage sags in the DFIG system including the rotor over-currents, electromagnetic torque oscillations, and DC-link over-voltage and also injects reactive power into grid to support the grid voltage. So, the LVRT capability of DFIG is enhanced and new grid code requirements are addressed. Simulation results on a 1.5-MW DFIG-based WECS using MATLAB/Simulink demonstrate the effectiveness of the proposed LVRT scheme under both balanced and unbalanced grid voltage sags.